2020
DOI: 10.1039/d0py00782j
|View full text |Cite
|
Sign up to set email alerts
|

Cationic amphiphilic alternating copolymers with tunable morphology

Abstract: A series of ionic amphiphilic alternating copolymers were characterized via SAXS, TEM and DLS to help understand factors that could potentially affect self-assembly, including the degree of polymerization, the length...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The ruthenium-catalyzed AROMP of low-strain cyclic olefins and bicylo[4.2.0]octenes has been investigated extensively and has been championed for producing copolymers that can display a variety of functional groups, controlled backbone sequences, and tunable material properties such as hydrophilicity and glass transition temperatures. , To prepare the [4.2.0] glycopolymers, 4,7-dihydro-1,3-dioxepin or cyclohexene (B monomer) was allowed to react with bicyclo[4.2.0]oct-6-ene-7-carboxamide bearing mannose or fucose (A monomer) in the presence of Grubbs’ third generation catalyst 4 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ruthenium-catalyzed AROMP of low-strain cyclic olefins and bicylo[4.2.0]octenes has been investigated extensively and has been championed for producing copolymers that can display a variety of functional groups, controlled backbone sequences, and tunable material properties such as hydrophilicity and glass transition temperatures. , To prepare the [4.2.0] glycopolymers, 4,7-dihydro-1,3-dioxepin or cyclohexene (B monomer) was allowed to react with bicyclo[4.2.0]oct-6-ene-7-carboxamide bearing mannose or fucose (A monomer) in the presence of Grubbs’ third generation catalyst 4 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Evolution in free radical polymerization and atom transfer radical polymerization has resulted in biocompatible polymers with increased water solubility and low cytotoxicity. The utilization of polycondensation or ring-opening polymerization to synthesize polyesters has inspired the development of biocompatible materials for dental, orthopedic, drug delivery, and heart regeneration applications. In our laboratory, we have applied alternating ring-opening metathesis polymerization (AROMP) methods to synthesize sequence-controlled polymers with tunable hydrophilicity, morphology, and degradability. …”
mentioning
confidence: 99%
“…Sequence specific copolymers, such as multiblocks and strictly alternating AB copolymers, are also believed to have a high potential in the field of MSR polymers 103 . The latter are more conveniently obtained through ring‐opening and step‐growth polymerizations 104–108 . However, Ameduri and co‐workers 109 optimized a RAFT protocol that affords an alternating copolymer of t ‐butyl‐2‐trifluoromethacrylate and VA in a one‐pot reaction, owing to the inability of MAF‐TBA radical to self‐propagate.…”
Section: Background: Matching Building Block Studs For Specific Compositions Architectures and Functionsmentioning
confidence: 99%
“…Ion-exchange membranes are of interest for electrochemical energy conversion technologies including fuel cells, electrolyzers, batteries, and redox flow batteries . Anion-exchange membranes (AEMs) specifically have been targeted as a promising material for all of these devices because alkaline systems allow for more facile catalysis and utilization of nonplatinum group metal (PGM) catalysts. , Block copolymer-based AEMs are of further interest due to their ability to self-assemble into phase-separated morphologies, which can ultimately lead to improvements in ion conduction and transport of reactant and product species across the membrane. While phase separation in neutral block copolymers is well understood, experimental and computational studies have shown charge effects in block polyelectrolytes significantly impact the Flory–Huggins parameter and phase diagram, where factors including chain length, charge fraction, charge size, and the strength of Coulombic interactions all impact morphology. …”
Section: Introductionmentioning
confidence: 99%